A modified household economic portfolio model for assessing impact of microfinance using diaries. Issue 1 (9th January 2017) - Alia, Hayyan; Ashta, Arvind; Ratsimalahelo, Zaka
Abstract : Purpose: Microfinance impact evaluation studies help in discovering client needs which are diverse, special and different from the needs of the conventional bankable clients. Thus, such area of market research is becoming essential for microfinance institutions for designing better client-centred products. In this research, the authors discuss the specific model of household economic portfolio (HEP) for qualitative impact evaluation in microfinance. The paper aims to discuss the complexity limitations of the HEP. Solutions are provided for overcoming these limitations. The modified household economic portfolio (M-HEP) model is simplified and detailed, and two types of diaries are suggested for implementing it. Design/methodology/approach: First, the authors briefly review the literature on impact assessment methods in microfinance and on the HEP model. In the second part of the paper, the M-HEP is suggested and discussed in detail. In the third part, the authors present a case study to illustrate the additional information that can be generated by using our suggested research tool and model. Finally, the authors wrap up with a summary of the findings. Findings: Solutions are provided for overcoming the limitations of the HEP model. The suggested model (M-HEP) is simplified and detailed, and two types of diaries are suggested for implementing it. The case study shows that, certainly, time and money are related. While time may mean money for a rich person, for a poor person, if money is not forthcoming, she may spend time on non-income generating work that adds to her social esteem. She may also consume inexpensive assets because spending time at low cost is important. Finally, she spends time in conducting activities for which she cannot afford to pay. Originality/value: The paper offers two novelties. First, it details the interactions between the elements of the HEP model of Chen and Dunn. This improvement to the original model is highly important for defining the measures that are required for redrawing the economic portfolio of an individual. The second novelty is in suggesting the collection of time-use and financial daily data. To the best of our knowledge, this is the first time a combined diary is used in microfinance research. These two novelties allow the application of a modified version of the highly interesting HEP model in spite of its complexity.